1971
DOI: 10.1002/1097-4679(197107)27:3<408::aid-jclp2270270331>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Client evaluation of therapist strength and positive-negative evaluation as related to client dynamics, objective ratings of competency and outcome

Abstract: were made by therapists and nurses in both years and by the patients themselves in the replication phase.Results supported the hypothesis that constricted patients are more likely to improve in this setting than are impulsive ones. The most consistently differentiating index was one of ego weakness (maladaptation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Some studies do indicate a significant positive correlation between therapist genuineness and outcome (Barrett-Lennard, 1962;Mitchell et al, 1973;Truax, Wargo, Frank, et al, 1966a;cf. Gross & DeRidder, 1966;Halkides, 1958;McClanahan, 1974;McNally, 1973;Melnick & Pierce, 1971;Rucker, 1983). Typical of findings associated with positive results is the study by Tausch et al (1970) in which genuineness (assessed by client report) strongly predicted outcome ( r = .51).…”
Section: Genuinenesslcongruencementioning
confidence: 99%
“…Some studies do indicate a significant positive correlation between therapist genuineness and outcome (Barrett-Lennard, 1962;Mitchell et al, 1973;Truax, Wargo, Frank, et al, 1966a;cf. Gross & DeRidder, 1966;Halkides, 1958;McClanahan, 1974;McNally, 1973;Melnick & Pierce, 1971;Rucker, 1983). Typical of findings associated with positive results is the study by Tausch et al (1970) in which genuineness (assessed by client report) strongly predicted outcome ( r = .51).…”
Section: Genuinenesslcongruencementioning
confidence: 99%
“…Using helpee perceptions of helper conditions has created some controversy. Burstein and Carkhuff (1968), Carkhuff and Burstein (1970), and Melnick and Pierce (1971) noted that clients typically distort their perceptions of facilitative conditions and therefore are not accurate judges. Recently Kaul, Kaul, and Bednar (1973) found that clients rated their own self-exploration higher than did either their counselors or trained raters.…”
Section: Rating Scalesmentioning
confidence: 99%